The Semantic Study of Ethics by Sheikh Eshraq - Hussein Ahmadi (آموزه‌‌های فلسفه اسلامي, 2022)
Ethics studies the principles of conceptualization and assent of the science of morality that includes the four following subjects: moral semantics, moral epistemology, moral ontology and the logical subjects of ethics. Moral semantics provides the study and semantic analysis of the concepts and moral propositions. Considering that the meaning of the sentence relates to the concepts of the sentence components meaning its subject matter (Arabic: موضوع mawdū‘) and predicate (Arabic: محمول mahmul), the major subjects that are stated in the moral semantics are to study concepts of the subject matter and predicate of the moral sentences. This paper aims to survey the semantics of the mentioned concepts with the analytic method through intellect from the viewpoint of Sheikh Eshraq. He has created the conceptual definition method in the moral semantics and has argued some ethical concepts but he has not mentioned how to get the meaning which constitutes the compound concepts and has not presented a solution for the semantics of the simple moral concepts for those who are not able the witnessing perception of the simple concepts. The solution alternative to this opinion is to notice the attributes of the philosophical concepts that the moral concepts are of these concepts. The most important attribute of the philosophical concepts is comparative and they are achieved by the mental attempt. It is important for the semantics of the moral concepts to compare between the act or the optional feature with the moral goal that the meaning of the mentioned concepts is obtained from this comparison.